Karakteristik Kesehatan Mental Remaja Dalam Perilaku Self Harm - Fajaruddin, Muhammad; Sahrul, Sahrul (Jayapangus Press, 2024)
Self-harm is known as self-harm is a mental health phenomenon in which a person uses physical pain to cope with emotional stress. The study aims to understand the characteristics of adolescent mental health with self-harm behavior, as well as to find out how adolescents can reduce self-harm behavior. This study applies a descriptive qualitative method. This study involved three informants with the initials DA, MAT, and FR. The informants in this study were adolescents aged 18-19 years who committed self-harm when facing problems. The determination of informants used a purposive sampling technique. Data collection techniques were obtained from observation, interviews, and documentation and were analyzed using the Miles and Huberman method. The characteristics of mental health possessed by adolescents with self-harm behavior in Village X tended more towards unhealthy mental characteristics. The results of the study showed adolescent behavior such as losing self-control in managing emotions, withdrawing from their environment, having feelings of shame and guilt, and difficulty concentrating in their social and school environments. In line with the opinions of experts regarding the characteristics of mental health which refer to an unhealthy mentality (ill mentality). However, even so, teenagers have tried to stop their self-harming behavior with other more positive activities such as exercising, writing and listening to music to please their hearts and minds.